Professional training from the axiological configuration of social responsibility in university management (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2017)
The purpose of this essay was aimed at reflecting on professional training from the axiological configuration of social responsibility in university management; for which a review of the theoretical aspects that explain the implications of the constructs related to an academic vision of classroom management was made, consistent with the teacher's task beyond the instructional to facilitate the training of professionals required by the country to assume a proactive, critical and reflective attitude towards the search for the conscience of socially responsible worth. The axiology as a theory of value, in addition to the philosophical positioning, has an existential reference inherent to the professional training reflected in the behaviors demonstrated in the actions of citizen participation, solidarity and ethical behavior to assume the increasingly complex environments where economic problems prevail, social and environmental factors that hinder the development of societies. Thus, university social responsibility alludes to the consistent commitment to the training of future professionals and the ways in which they will work in companies from an ethical, responsible perspective that contributes to the common good and social justice. It was concluded from an axiological view that values such as fraternity, solidarity, and social responsibility should guide the academic work aimed at achieving honest and honest citizens committed to the society of which they are a part and to which they will turn their knowledge to improve their quality of life, trying to solve the problems that the knowledge society faces.
Keywords: axiology; professional training; university management; social responsibility